The prevalence of Black/African American individuals in concussion literature: a systematic review and meta-analysis - MacEachern, Taia; John-Baptiste, Ava; Christie, Anita (Frontiers in Public Health, 2024)
Introduction Comprising approximately 13.6% of the United States population, Black/African American individuals are overrepresented in sports associated with a high risk of concussion. However, there has been a notable absence of systematic reviews examining whether concussion literature accurately reflects the participation and experiences of Black/African American individuals. Therefore, this study aims to systematically review the prevalence of Black/African American individuals compared to White individuals diagnosed with concussions in the literature. Methods A systematic search was performed across four electronic databases: PubMed, MEDLINE (Ovid), Scopus and Web of Science. Articles were searched from inception to January 5, 2022. Prevalence data were extracted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A meta-analysis of proportions was conducted within hospital records and national survey data. Results Among 447 identified studies, 11 were included, representing 1,839,901 individuals diagnosed with a concussion, with 73.6% identifying as White and 12.5% identifying as Black/African American. The mean proportion of Black/African American diagnosed with a concussion in hospital records (13.9%; 95% CI [12.8, 15.1]) exceeded that in national surveys (6.4%; 95% CI [3.5, 11.3]) but lower than sports-centered studies (16%). Discussion These findings underscore the need to address racial disparities in healthcare within the broader context of social determinants of health and systemic inequities. By identifying gaps in the current research, this study lays the foundation for future investigation aimed at elucidating and addressing healthcare disparities.